Analysis of Potential, Attraction, and Tourist Perception of Limpakuwus Pine Forest Natural Tourism, Banyumas City - Utami, Alya; Iqbal, Achmad; Rahab, Rahab (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Abstract: Development of the tourism sector can have an impact on the economic and environmental sectors. Tourism development is expected to balance in all sectors and not have a negative impact on the environment. Various tourism attributes such as accessibility, facilities and services can form tourist perceptions that can be used as a basis for evaluating tourism management and development. Limpakuwus Pine Forest Natural Tourism has great potential because it covers an area of 25 hectares, located in the highlands, has a cool climate, and beautiful natural scenery. The purpose of this research are identify the potential and tourism object attraction and also identify tourist perception about tourim’s condition. The research methodology uses mix method by observation and interview with the tour manager and tourist. The method which uses are qualitative and quantitative descriptive with likert scale. Result of this research appoint that Limpakuwus Pine Forest Natural Tourism have a good potential and attraction to be developed in terms of flora and fauna, facilities and infrastructure, tourist attraction, accessibility, and human resources. Tourist perception about tourism’s condition be regarder quite good, with a few records of improvements in multiple assessments. Natural tourism have a big potential to actualize the sustainable tourism, however still need further participation against managing the enviromental from all tourism subject.